Analisis Rekonsiliasi Fiskal Laporan Keuangan PT. SME Dalam Menentukan Pajak Penghasilan Terutang - Marcella, Gracia; Widjaja, Purnamawati Helen (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The intention of this research was to interpret the fiscal reconciliation of PT. SME financial statement in deciding income tax payable and make sure that the arrangement of company’s financial statement is properly accurate according to Taxation Law. The subject of this research was the company that is known to be PT. SME. The object used in this resarch was company’s commercial financial statement and fiscal financial statement for the period of 2021. The research design of this study was qualitative analysis. Data assemble methods in this study are the Library Research method and the Field Research. The study shows that some accounts of profit and loss haven’t been done a fiscal correction that will cause to an incorrect calculation of 2021 company’s income tax payable so that the dissimilarity could happen between the accumulation of income tax due according to IAS and Taxation Law related.